ADSORPSI ZAT WARNA TEKSTIL PADA ZEOLIT ALAM DARI BAYAH - Hilyati Hilyati; BAMBANG WIDIHASTONO (Jurnal Kimia Terapan Indonesia, 1991)
Adsorption equilibrium of a dye stuff (Basacryl Red X. GRL 300% of BASF) on a natural zeolite from Bayah was investigated by studying the effects of dye concentrations, panicle sizes of adsorbent, agitation rates and adsorption temperatures. The experimental results indicated that adsorption follows the Langmuir and Freundlich equations. Adsorption of dye stuff into the zeolite increased by decreasing the adsorbent panicle size and by increasing both temperature and agitation rate. The adsorption ability of the natural zeolite could be increased up to 5-7 % higher than inactroated zeolite via an aktivation proces by treating it with H2SO4, HCL, HNO3, NaOH or heating seperately. It is found that the maximum adsorption by zeolite occured at the base or acid concentration of 0,05 N, or at temperature of 100°C.